WAHDAH AL-WUJUD DALAM KONTEKS AKIDAH DAN TASAWWUF DI MALAYSIA - Ahmad Najaa Mokhtar; Muhammad Khairi Mahyuddin; Hamidi Ismail; Yuseri Ahmad; Ahmad Alaa Mokhtar (IAI Al-Mawaddah Warrahmah Kolaka, 2019)
The debate on the issue of wahdatul wujud has long been in force among scholars. In Malaysia, this issue is associated with aqeedah which is then half the country's pleasure forbids teaching and practice wahdatul wujud. However, the discussion of wahdatul wujud needs to be refined by looking at it from a different perspective, from the perspective of aqeedah and Sufism. Although the two sciences have different disciplines, this study will outline the point of reflection and meeting to harmonize understanding of the term. With that, the main objective of this study is to understand the concept of wahdatul wujud, the differences of views of the ulama and to harmonize these views with the approach of the discipline of faith and Sufism. Therefore, this study uses the methodology of historical and textual analysis of the books of the aqidah and tasawwuf fields. Obtained is the description of wahdatul form according to some ulema of the faith by looking at the point of view of other religions and compared with the term wahdatul form, while, Tasawwuf scholars also see the term with other intentions that are not related to the concept of hulul and ittihad. Exactly, mistakes and tensions that appear to have been incurred are caused by the terminology which is translated with incorrect translations. Therefore, the term wahdatul wujud needs to be explained correctly and precisely. This case may be resolved by perfecting scientific disciplines on the basis of clearer Islamic Shari'a.